Grain size effect on the electrical response of SnO2 thin and thick film gas sensors - Savu, Raluca [UNESP]; Ponce, Miguel Adolfo; Joanni, Ednan [UNESP]; Bueno, Paulo Roberto [UNESP]; Castro, Miriam; Cilense, Mario [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (ABM, ABC, ABPol, 2009)
Porous nano and micro crystalline tin oxide films were deposited by RF Magnetron Sputtering and doctor blade techniques, respectively. Electrical resistance and impedance spectroscopy measurements, as a function of temperature and atmosphere, were performed in order to determine the influence of the microstructure and working conditions over the electrical response of the sensors. The conductivity of all samples increases with the temperature and decreases in oxygen, as expected for an n-type semiconducting material. The impedance plots indicated the existence of two time constants related to the grains and the grain boundaries. The Nyquist diagrams at low frequencies revealed the changes that took place in the grain boundary region, with the contribution of the grains being indicated by the formation of a second semicircle at high frequencies. The better sensing performance of the doctor bladed samples can be explained by their lower initial resistance values, bigger grain sizes and higher porosity.
Keywords: semiconductors; impedance spectroscopy; electrical propertie